Hybrid type generalized multivalued vector complementarity problems - Agarwal, P.; Ahmad, M. K.; Salahuddin (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We introduce a new type of generalized multivalued vector complementarity problems with moving pointed cone. We discuss the existence results for generalized multivalued vector complementarity problems under inclusive assumptions and obtain results on the equivalence between the generalized multivalued vector complementarity problems and the generalized multivalued vector variational inequality problems.